2014
DOI: 10.1002/app.40472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amino‐functionalized carbon nanotubes on the properties of amine‐terminated butadiene–acrylonitrile rubber‐toughened epoxy resins

Abstract: Amino-functionalized multiwalled carbon nanotubes (MWCNT-NH 2 s) as nanofillers were incorporated into diglycidyl ether of bisphenol A (DGEBA) toughened with amine-terminated butadiene-acrylonitrile (ATBN). The curing kinetics, glasstransition temperature (T g ), thermal stability, mechanical properties, and morphology of DGEBA/ATBN/MWCNT-NH 2 nanocomposites were investigated by differential scanning calorimetry (DSC), thermogravimetric analysis, a universal test machine, and scanning electron microscopy. DSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…However, results reported by others shows that the addition of 10 wt% Mg(OH) 2 leads to a slight decrease of T g value (4°C) [26]. It is well known that the effects of the presence of fillers on the T g of polymer matrix is related to the rigid phase reinforcement and crosslinking network of the thermosetting polymer matrix [27][28][29]. Unlike the halogen-free reactive flame retardant, DOPO [30], the addition of brucites has negligible influence on the crosslinking networks of epoxy resin.…”
Section: Glass Transition Temperaturementioning
confidence: 93%
“…However, results reported by others shows that the addition of 10 wt% Mg(OH) 2 leads to a slight decrease of T g value (4°C) [26]. It is well known that the effects of the presence of fillers on the T g of polymer matrix is related to the rigid phase reinforcement and crosslinking network of the thermosetting polymer matrix [27][28][29]. Unlike the halogen-free reactive flame retardant, DOPO [30], the addition of brucites has negligible influence on the crosslinking networks of epoxy resin.…”
Section: Glass Transition Temperaturementioning
confidence: 93%
“…10,11 To achieve further improvement in the fracture toughness without a sacrifice in other desirable properties, the simultaneous addition of rubber and rigid particles, especially on the nanoscale, into the epoxy resin has been proposed. 12,13 In this regard, the use of soft rubber particles in combination with nanoclay, 14 nanosilica, 15 and carbon nanotubes 16 has been reported, although these different studies did not achieve the same result from the view of improving the fracture toughness of the hybrid system in comparison to their corresponding binary composites. [17][18][19][20][21] For instance, Marouf et al 17 reported that the fracture toughness of a hybrid epoxy modified with clay and rubber nanoparticles was lower than that of its binary composite counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The marginal improvement in properties was attributed to the presence of fCNT agglomerates in the sample due to inefficient mixing. Similarly, Zhang et al reported that addition of amine fCNT to RTE led to marginal increase in tensile strength and flexural strength, by 14% and 10%, respectively. However, Huang et al demonstrated significant improvement in fracture toughness of epoxy with addition of liquid‐rubber‐functionalized graphene and use of highly efficient mixing protocols (ultrasonication + three roll mill calendaring) while only moderate improvement was noticed with non‐functionalized graphene processed under similar conditions.…”
Section: Introductionmentioning
confidence: 90%